Overcoming the Three-Dimensional Complexity of Vulvar Defects: A Stepwise, Multi-Flap Approach - Ang, Chuan-Han; Tan, Walter J.X.; Tan, Bien-Keem; Chew, Khong-Yik (Archives of Plastic Surgery, 2025)
Complex vulvar defects are challenging owing to their three-dimensional characteristics. We introduce a combined flap approach to maximize the use of locoregional tissues. Four patients had defects involving the vaginal wall, anal canal, and perineum, with a size range of 108 to 157 cm2. The outcomes were analyzed using a questionnaire regarding micturition, defecation, coital function, introitus opening, and aesthetics. For the vulva, the gluteal fold flap was the primary flap, which was augmented by the mons pubis rotation flap, gracilis muscle flap, pudendal thigh flap, and medial thigh VY advancement flap. The perianal skin and anal defects were covered by the gluteal fold and buttock VY advancement flaps. Patients' satisfaction scores were favorable on follow-up. Our multi-flap approach optimized the aesthetic and functional results of combined vulvar–anal defects.
Keywords: extramammary Paget's disease; squamous cell carcinoma; vulvar reconstruction